Non-Dimensional Number Analysis on Natural Circulation Flow Changes Inside Straight-Pipe Heat Exchanger of Water Cooling Tank in FASSIP-02 Test Loop - Arista, E. P.; Deendarlianto, D; Al-amin, A. S.; Setiawan, P. H.; Gunawan, H. A.; Juarsa, M. (Atom Indonesia, 2024)
The FASSIP-02 test loop is a large-scale experimental facility that investigates natural circulation flow rate phenomena to improve passive safety systems of nuclear reactors. Heat transfer in the piping system will result in pattern and magnitude of the natural circulation flow being formed, so it is essential to investigate the heat dissipation capabilities, which will later be applied in nuclear passive cooling systems. The heat transfer behavior of passive cooling systems in large-scale facilities can be quantified with non-dimensional numbers. This research analyzes heat transfer in a straight heat exchanger by comparing non-dimensional numbers based on the Dittus-Boetler and McAdams correlation with the correlation generated from experimental data. The analysis results show that the predicted McAdams correlation with the experimental correlation is higher than 83 %. Meanwhile, Dittus Boetler's correlation prediction with the experimental correlation is smaller than 71 %. The dominance of momentum diffusivity in the cooling process shows the characteristics of thermal behavior with the Prandtl number. In addition, all-natural circulation flow variations occur in a turbulent flow regime that increases with increasing water temperature in the heating tank.